The Effectiveness of Audit Guideline Using Directive Discourse for Control and Prevention of Methicillin Resistant Staphylococcus aureus Infection - Kusbaryanto Kusbaryanto; K. Kuntaman; WJ. Pudjirahardjo (Intelektual Pustaka Media Utama, 2016)
Methicillin Resistant Staphylococcus aureus (MRSA) infection is one of the major problems in the hospital, due to its increasing of prevalence. The aim of this study was to analyze the effectiveness of the Audit Guideline for control and prevention of MRSA infection, using directive discourse on nurses in hospitals. The Audit Guideline was focused on its effectiveness in improving the situation awareness of the nurses. This study was a quasi-experimental study using a pretest-posttest control group design. The population was ward nurses in a hospital. The samples were taken from four medical wards, two wards as the treatment group (25 nurses) and two wards as the control group (28 nurses). The two groups get the training of MRSA infection control and prevention. The training of the guideline of MRSA infection control and prevention using directive discourse was only applied in the treatment group. The analysis of the results of the situation awareness action was conducted, and the result of situation awareness action was improved from 0.8 response to 1.8 response (p = 0.014). This result was significantly difference because of the training using Audit Guideline for MRSA infections control and prevention with directive discourse become a positive reinforcement, the positive driven to stimulate behavior change of the nurses.